Switzerland : Financial System Stability Assessment Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This technical note presents an update to the Financial System Stability Assessment (FSSA) on Switzerland. It reveals that current domestic macroeconomic and financial sector conditions are favorable, and the main downside risks to the financial sector are external. Stress tests confirm the banking system's resiliency but that some insurers are vulnerable to market risks. Several pension funds are underfunded and need to strengthen their funding levels. Impressive progress has been made to strengthen the financial sector supervisory framework since the 2001 Financial Sector Assessment Program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet